2005
DOI: 10.1182/blood-2003-03-0772
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C protects HL60 and U266 cells from arsenic toxicity

Abstract: Although there is no compelling evidence that vitamin C has antitumor activity in humans, clinical trials are testing the hypothesis that ascorbic acid (AA) will enhance the efficacy of arsenic trioxide (As 2 O 3 ) in myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 71 publications
(109 reference statements)
5
37
0
Order By: Relevance
“…We quantified peroxide-equivalents in ES cell medium, which had been spiked with increasing amounts of AA, or its oxidized intermediate, dehydroascorbic acid (DHA). Consistent with previous results [24], AA but not DHA, dosedependently increased peroxide levels in both high and low glucose medium, with 500 lM AA releasing $10 lM peroxide after incubation for 60 minutes (Fig. 4D).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We quantified peroxide-equivalents in ES cell medium, which had been spiked with increasing amounts of AA, or its oxidized intermediate, dehydroascorbic acid (DHA). Consistent with previous results [24], AA but not DHA, dosedependently increased peroxide levels in both high and low glucose medium, with 500 lM AA releasing $10 lM peroxide after incubation for 60 minutes (Fig. 4D).…”
Section: Resultssupporting
confidence: 92%
“…Although the mechanism of action was not addressed in their original publication [34], Takahashi et al suggested that the role of AA in cardiomyogenesis was unrelated to its intrinsic antioxidant properties, as other antioxidants failed to reproduce the effects in the experimental system. Paradoxically, AA has been shown to have pro-oxidant properties in the presence of transition metals found in tissue culture media [24]. We thought it reasonable to postulate that AA could remove the cardiomyocyte block in low glucose-differentiated EBs by increasing levels of ROS.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…21,22 Although in vivo effects have been reported for this combination, 23 the observed additive toxicity may not be selective for cancer cells, and BSO itself has not been successfully developed for clinical use. Ascorbic acid (AA), a key antioxidant molecule, augments the toxicity of As 2 O 3 in vitro, 24,25 but controversy exists regarding its mechanism of action, 26 and its potential for utility in the clinic is under study.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is an environmental toxin but it has also been used in medicine as a therapeutic agent for more than 2400 years. [2] Inorganic arsenic is now a first choice cancer chemotherapeutic against certain leukemia. [3], [4] The US Food and Drug Administration (FDA) approved the use of Trisenox brand arsenic trioxide (As 2 O 3 ) for the treatment of acute promyelocytic leukemia in September 2000.…”
Section: Introductionmentioning
confidence: 99%